2019
DOI: 10.1186/s13045-019-0777-7
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA GSTM3TV2 upregulates LAT2 and OLR1 by competitively sponging let-7 to promote gemcitabine resistance in pancreatic cancer

Abstract: Background Chemoresistance is one of the main causes of poor prognosis in pancreatic cancer patients. Understanding the mechanisms implicated in chemoresistance of pancreatic cancer is critical to improving patient outcomes. Recent evidences indicate that the long noncoding RNAs (lncRNAs) are involving in chemoresistance of pancreatic cancer. However, the mechanisms of lncRNAs contribute to resistance in pancreatic cancer and remain largely unknown. The objective of this study is to construct a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 43 publications
3
80
0
Order By: Relevance
“…in the cell cytoplasm, lncRNA GSTM3TV2 served as ceRNA to up-regulate LAT2 and OLR1 expression, promoting gemcitabine resistance in pancreatic cancer. In the current study, we found that miR-214 was a direct target miRNA of FAM83A-AS1 in ESCC [33]. It was reported that miR-214 inhibited cell proliferation, migration, and invasion process in ESCC [20].…”
Section: Discussionsupporting
confidence: 48%
“…in the cell cytoplasm, lncRNA GSTM3TV2 served as ceRNA to up-regulate LAT2 and OLR1 expression, promoting gemcitabine resistance in pancreatic cancer. In the current study, we found that miR-214 was a direct target miRNA of FAM83A-AS1 in ESCC [33]. It was reported that miR-214 inhibited cell proliferation, migration, and invasion process in ESCC [20].…”
Section: Discussionsupporting
confidence: 48%
“…Therefore, these results may also be regulation [33]. Moreover, lncRNAs play a role through the competitive binding of miRNAs to regulate their target mRNAs [34].…”
Section: Discussionmentioning
confidence: 97%
“…In addition, HOTAIR promotes the invasion of breast cancer cells by affecting the expression of cell surface glycosaminoglycans [13]. The lncRNA Homo sapiens glutathione S-transferase mu 3, transcript variant 2 and noncoding RNA (GSTM3TV2) levels are significantly increased in pancreatic tumor tissues and it upregulates the L-type amino acid transporter 2 (LAT2) and oxidized low-density lipoprotein receptor 1(OLR1) by competitively sequestering let-7 (a mRNA targeting c-Myc, HMGA2 and Ras) to induce gemcitabine resistance in pancreatic cancer [15].…”
Section: Introductionmentioning
confidence: 99%